Integrating Local Culture Into English Teaching Materials: An Analysis of Teachers’ Needs in Islamic Junior High Schools - Rustam, Utary; Kalsum; Rustam, Wahyu (Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia, 2025)
Integrating local culture into English language teaching has been widely recognized as a means of enhancing students’ engagement and cultural relevance in learning. This study investigates English teachers’ pedagogical, resource-related, and professional development needs in integrating local culture into English teaching materials in Islamic junior high schools in Indonesia. Employing a descriptive qualitative design, the study involved semi-structured interviews with eight English teachers. The interview protocols were informed by three theoretical frameworks: Pedagogical Content Knowledge (PCK), Funds of Knowledge, and Culturally Relevant Pedagogy (CRP). Data were analyzed thematically through systematic coding, category development, and theme refinement. The findings reveal three interrelated needs. First, although teachers recognize the pedagogical value of local culture, they experience difficulties in translating cultural content into communicative instructional practices, indicating limitations in their pedagogical content knowledge. Second, teachers face restricted access to culturally relevant resources, particularly materials representing Bugis culture, which constrains the effective utilization of their funds of knowledge. Third, despite strong motivation to integrate local culture, teachers report limited access to targeted professional training, underscoring the need for CRP-informed professional development. The study highlights the importance of sustained institutional support and collaborative professional learning opportunities to strengthen culturally responsive English teaching practices in Islamic secondary education.